Ethical issues in maternal-fetal medicine - Dickenson, Donna (Cambridge University Press, 2002)
This book addresses the ethical problems in maternal-fetal medicine which impact directly on clinical practice. It is divided into parts by the stages of pregnancy and looks at issues of power, new technology, 'designer babies', and cultural, religious difference. It unites analytic philosophy and actual practice for clinicians.